Integrated Administrative Data & Criminal Justice Research - DeHart, Dana (American journal of criminal justice, 2017)
Using integrated administrative data from criminal justice and social service systems can harness information in meaningful ways that transcend traditional “silos” and allow communities to focus collective attention on important social issues that cross systemic boundaries. Despite recent advances in use of integrated administrative data, practical information to promote adoption by new users is lacking. Here we provide an introduction to potential uses of integrated administrative data for criminal justice researchers, including general benefits of using integrated data as well as implications for innovative research design. We describe a case example of data integration through a state data warehouse for a federally funded project on impact of incarceration on families. The project utilizes data from eight agencies (corrections, juvenile justice, mental health, substance use, social services, health, education, and environmental control) and includes development of an Online Analytical Processing cube. We draw from lessons learned to provide specific recommendations for developing researcher-practitioner partnerships that use integrated administrative data to improve translational criminal justice research and evidence-based practice and policy.